Marijuana Use Is Not Associated With Changes in Opioid Prescriptions or Pain Severity Among People Living With HIV and Chronic Pain. (1st June 2019) - Merlin, Jessica S.; Long, Dustin; Becker, William C.; Cachay, Edward R.; Christopolous, Katerina A.; Claborn, Kasey R.; Crane, Heidi M.; Edelman, Eva Jennifer; Lovejoy, Travis I.; Mathews, William Christopher; Morasco, Benjamin J.; Napravnik, Sonia; et al.
Abstract : Background: People living with HIV (PLWH) commonly report marijuana use for chronic pain, although there is limited empirical evidence to support its use. There is hope that marijuana may reduce prescription opioid use. Our objective was to investigate whether marijuana use among PLWH who have chronic pain is associated with changes in pain severity and prescribed opioid use (prescribed opioid initiation and discontinuation). Methods: Participants completed self-report measures of chronic pain and marijuana use at an index visit and were followed up for 1 year in the Center for AIDS Research Network of Integrated Clinical Systems (CNICS). Self-reported marijuana use was the exposure variable. Outcome variables were changes in pain and initiation or discontinuation of opioids during the study period. The relationship between exposure and outcomes was assessed using generalized linear models for pain and multivariable binary logistic regression models for opioid initiation/discontinuation. Results: Of 433 PLWH and chronic pain, 28% reported marijuana use in the past 3 months. Median pain severity at the index visit was 6.3/10 (interquartile range 4.7–8.0). Neither increases nor decreases in marijuana use were associated with changes in pain severity, and marijuana use was not associated with either lower odds of opioid initiation or higher odds of opioid discontinuation. Conclusions: We did not find evidence that marijuana use in PLWH is associated with improved pain outcomes or reduced opioid prescribing. This suggests that caution is warranted when counseling PLWH about potential benefits of recreational or medical marijuana.